Pengaruh Kualitas Informasi terhadap Niat Pembelian Kembali Konsumen pada E-Commerce - Remizar Fahrezi Achyar Firdaus; Diah Priharsari; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Mobile technology is currently increasing every time so that it can create innovation and also technology adoption. One of the impacts of the existence of technology is in terms of buying and selling transactions. Nowadays, buying and selling online activities have become a common thing for everyone. Customer repurchase intentions of a product company or service is one thing that the company expects. It is not easy for companies to be able to create repurchase intentions for customers. Several factors that can influence the intention of repurchase customers are satisfaction and trust as well as trust and satisfaction of these customers by the quality of the information. This research aims to determine how the influence of information quality on consumers' repurchase intentions in e-commerce. In addition, this study also explains how the influence of user satisfaction and customer loyalty on consumers' repurchase intentions. This study uses the SEM-CB method by distributing questionnaires to 326 respondents. From the results of the research that has been done, it was found that one of the hypotheses that was declared not accepted was customer satisfaction with repurchase intentions with a P-Value of 0.116. There's too many sellers in e-commerce, it will make the buyers have many options for benchmarking before repurchasing a product.